Adipocytes-Derived Extracellular Vesicle-miR-26b Promotes Apoptosis of Cumulus Cells and Induces Polycystic Ovary Syndrome - Zhou, Guannan; Gu, Yuanyuan; Zhou, Fangyue; Zhang, Hongdao; Zhang, Menglei; Zhang, Ganrong; Wu, Ligang; Hua, Keqin; Ding, Jingxin (Frontiers in Endocrinology, 2022)
Background: Polycystic ovary syndrome (PCOS) is a refractory reproductive disease and also a kind of endocrine and metabolic disease. Adipocyte cells can produce a mass of extracellular vesicles and orchestrate the status of other types cells. The objective of this study was to determine the effects of adipocyte derived extracellular vesicles-miR-26b on cumulus cells (CCs) and development of PCOS. Methods: The crosstalk mediated by extracellular vesicle-miR-26b between adipocytes and CCs was determined in CC cells co-cultured with mature adipocytes or incubated with extracellular vesicle isolated from mature adipocytes. CCK-8 assay and flow cytometry were conducted in CCs treated with or without extracellular vesicles, miRNA sequencing was conducted for clarifying the key molecular. Hormone levels and ovary ovulation ability were conducted with animal experiment. Results: The results revealed that miR-26b was upregulated in extracellular vesicles derived from mature adipocytes. Adipocyte derived extracellular vesicles inhibited viability and promoted apoptosis in CCs via targeting JAG1. Furthermore, extracellular vesicles derived from mature adipocyte disrupted the ovary ovulation, as well as impaired the hormone levels. Conclusions: These results identify a novel signaling pathway that adipocytes derived extracellular vesicles-miR-26b promotes cell apoptosis in CCs and disrupted the ovary ovulation in the development of PCOS. The study indicates that adipose tissue-derived extracellular vesicles-miR-26b may play a key role in the PCOS, and also provides insight into developing new therapeutic strategies for PCOS.